2019
DOI: 10.1371/journal.pone.0224823
|View full text |Cite
|
Sign up to set email alerts
|

One-year follow-up of changes in refraction and aberrations induced by corneal incision

Abstract: PurposeTo evaluate the surgically induced changes in refraction (sphere and astigmatism) and higher order aberrations by corneal incision for one year.SettingUniversity Hospital “Virgen de la Arrixaca”, Murcia, Spain.DesignRetrospective interventional case series.MethodsCorneal power, astigmatism and higher order aberrations (HOA) were calculated from corneal topography measured in 27 eyes prior to surgery and at 2 weeks, 1, 2, 3 and 6 months and 1 year following cataract surgery with 3.2-mm corneal incision. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…In the toric IOL group, the mean reduction of corneal astigmatism was 0.20 D from topography and 0.32 D from the automated keratometer at the 1-month follow-up, which dropped to 0.07 D from topography and 0.13 D from the automated keratometer at the 6-month follow-up. These changes can be attributed to the effect of surgically induced astigmatism, and our results are consistent with results of previous studies [ 31 , 32 ]. Obviously, compared to baseline preoperative levels, the amount of reduction was not significant in the toric IOL group, while significant reduction of corneal astigmatism was noted in the AK group.…”
Section: Discussionsupporting
confidence: 94%
“…In the toric IOL group, the mean reduction of corneal astigmatism was 0.20 D from topography and 0.32 D from the automated keratometer at the 1-month follow-up, which dropped to 0.07 D from topography and 0.13 D from the automated keratometer at the 6-month follow-up. These changes can be attributed to the effect of surgically induced astigmatism, and our results are consistent with results of previous studies [ 31 , 32 ]. Obviously, compared to baseline preoperative levels, the amount of reduction was not significant in the toric IOL group, while significant reduction of corneal astigmatism was noted in the AK group.…”
Section: Discussionsupporting
confidence: 94%
“…Because OHB is one of the late complications, in our study, all cases were analyzed 3 months or more after TLE. Like cataract surgery, as for small-incision cataract surgery, changes in corneal aberrations may occur early after surgery; however, these changes gradually returned to preoperative values by 2 or 3 months after surgery [ 29 , 30 , 31 ]. In our study, all cataract surgeries were performed with small incisions using a phacoemulsification platform, and all cataract surgery cases were measured 3 months or more after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] In this study, the ocular HOAs decreased signi cantly after surgery, which indicated an increase of visual quality with mulitifocal IOL implantation. It has been shown that corneal incisions can increase the values of the root mean square (RMS) of corneal HOAs [22][23][24][25] ; thus, we assessed the changes in corneal aberrations after surgery. The wavefront parameters of total HOAs, trefoil, coma, spherical aberrations, and secondary astigmatism were compared, since these aberrations constitute the major components of HOAs.…”
Section: Discussionmentioning
confidence: 99%